Awakening Effect of Transcranial Magnetic Stimulation with Multimodal Magnetic Resonance Imaging under Three-Dimensional Reconstruction Algorithm Combined with Wake-Up Nursing on Patients with Massive Cerebral Infarction. (6th July 2022) - Chen, Bocan; Li, Li; Ji, Xiaoxia
Abstract : This study was aimed to provide arousal treatment for disturbance of consciousness in patients with massive cerebral infarction, using multimodal magnetic resonance imaging (MRI)-assisted transcranial magnetic stimulation (TMS) under three-dimensional reconstruction algorithm combined with wake-up nursing. The application effect was also evaluated. 80 patients with massive cerebral infarction were selected as the research objects. These patients were divided into the control group (routine nursing and TMS) and the experimental group (routine nursing, multisensory stimulation wake-up nursing, and TMS) according to the even- and odd-numbered admission orders. There were 40 cases in each group, and the treatment effects of the two groups were compared and analyzed. The peak signal-to-noise ratio (PSNR) (800 dB) of the bilateral filtering algorithm was higher than that of the wavelet threshold denoising (321 dB) and the nonlocal mean filtering algorithm (455 dB). The segmentation accuracy of the improved region growing method/fuzzy spatial clustering algorithm (96.21% and 97.22%) was higher than that of the unimproved ones (82.11% and 79.99%). The Glasgow Coma Scale (GCS), Coma Recovery Scale-Revised (CRS-R), and Dysfunction Scale (DFS) scores of the experimental group were significantly higher than those of the control group 1 week and 2 weeks after treatment (P < 0.05 ). The awakening rate of patients in the experimental group (95%) was also significantly higher than that in the control group (72.5%), and the time needed for waking up was (2.28 ± 2.92) hours, lower than that in the control group (4.34 ± 3.49) hours (P < 0.05 ). The three-dimensional reconstruction algorithm could effectively improve the display effect of MRI images and assist in the examination of diseases. Multisensory stimulation wake-up nursing combined with TMS could promote patients to wake up more quickly and help the recovery of brain function of patients in the treatment of massive cerebral infarction and disturbance of consciousness.